2012
DOI: 10.1155/2012/720474
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Saturation Flow Rates at Signalized Intersections

Abstract: The saturation flow rate is a fundamental parameter to measure the intersection capacity and time the traffic signals. However, it is revealed that traditional methods which are mainly developed using the average value of observed queue discharge headways to estimate the saturation headway might lead to underestimate saturation flow rate. The goal of this paper is to study the stochastic nature of queue discharge headways and to develop a more accurate estimate method for saturation headway and saturation flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…One more study [11], observed that regression model developed to estimate saturation flow showed good correlation with field value. Study [12], conducted at Beijing revealed that for different signalized intersections, the queue discharge headway distribution are often not identical.…”
Section: Study Of Saturation Flow Rate Of Signalized Intersectionsmentioning
confidence: 99%
“…One more study [11], observed that regression model developed to estimate saturation flow showed good correlation with field value. Study [12], conducted at Beijing revealed that for different signalized intersections, the queue discharge headway distribution are often not identical.…”
Section: Study Of Saturation Flow Rate Of Signalized Intersectionsmentioning
confidence: 99%
“…To determine the number of vehicles that can be dispatched in a given green time interval, we make use of saturation headway [49]. When the traffic light for a lane turns from red to green, the leading vehicle takes a longer time (h 1 ) to react to the change in traffic lights.…”
Section: Traffic Modelmentioning
confidence: 99%
“…Three categories of vehicle and nine types of headways were considered with the possible combination followed by linearly regressed saturation f low model. (Shao and Liu, 2012) studied stochastic nature of queue discharge headways. In their study, Distribution characteristics of headways were not considered and there was no consistency between both distributions applied to the headways (at 95% significance level).…”
Section: Saturation Flow Modelsmentioning
confidence: 99%